Konflikty cywilizacyjne a prawa człowieka. Wybrane aspekty problematyki - Ferenc-Kopec, Dorota (PRAWO i WIĘŹ, 2025)
This paper examines the impact of civilizational conflicts on human rights, focusing on the growing cultural and religious diversity in the era of globalization. It examines how the clash of different value systems, legal norms, and social practices leads to tensions and human rights violations. The challenges that universal human rights standards face when they encounter resistance from local legal systems, often based on traditional and conservative values, are highlighted. The problem of cultural relativism as a potential obstacle to the implementation of these standards is also discussed. The changing role of culture and religion in the contemporary world is analysed, as is the complexity of clashes of civilisations and the need to consider them in a wider political, historical and economic context.